2022
DOI: 10.3390/ijerph191912807
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality Impacts Survivorship: Identity-Informed Recommendations to Improve the Quality of Life of African American Breast Cancer Survivors in Health Promotion Programming

Abstract: (1) Background: African American women breast cancer survivors face unique experiences that impact their quality of life as they transition beyond treatments. Experiences may be complicated by living at the intersection of systemically oppressed identities, including gender, race, social class, and cancer-related disability. Using the Black Feminist Thought (BFT) framework and the PEN-3 cultural model, this qualitative study sought to: (a) understand African American women breast cancer survivors’ lived experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Most BCS who have limited income, are racial and ethnic minorities and receive care in public health systems lack access to and underutilize survivorship care resources even when these resources are available [17,18]. In addition, they are more likely to experience racial discrimination [15,19]. Latina BCS experience worse HRQOL and higher levels of pain, fatigue, and depressive symptoms as compared to White women [5,12] Furthermore, they are less likely to receive survivorship care services such as survivorship care information [20,21] and more likely to report unmet symptom needs [22].…”
Section: Introductionmentioning
confidence: 99%
“…Most BCS who have limited income, are racial and ethnic minorities and receive care in public health systems lack access to and underutilize survivorship care resources even when these resources are available [17,18]. In addition, they are more likely to experience racial discrimination [15,19]. Latina BCS experience worse HRQOL and higher levels of pain, fatigue, and depressive symptoms as compared to White women [5,12] Furthermore, they are less likely to receive survivorship care services such as survivorship care information [20,21] and more likely to report unmet symptom needs [22].…”
Section: Introductionmentioning
confidence: 99%
“…The value and impact of medical advocacy to achieve breast cancer equity has been increasingly studied [10][11][12] including among African American survivors and other marginalized populations [7,[12][13][14][15][16][17][18][19]. Past research has identified potentially universal experiences across racial and ethnic groups (e.g., reciprocity, or the value of "giving back") and culturally specific experiences with medical advocacy (e.g., navigating community mistrust, the need for minority breast health spaces/support groups).…”
Section: Introductionmentioning
confidence: 99%